2023
DOI: 10.26858/ijole.v7i2.46431
|View full text |Cite
|
Sign up to set email alerts
|

Grammarly and Grammatical Errors Reduction: A Case for Non-Native English Teachers’ Professional Learning

I G A Lokita Purnamika Utami,
I Gusti Ngurah Agung Wijaya Mahardika

Abstract: Grammar has long been a source of aggravation for anyone learning a second language, not just English language learners, but also non-native English teachers. People can now employ Grammarly to correct their grammar mistakes, owing to the sophistication of modern technology. The debate over whether teachers use Grammarly as part of their professional development is ongoing. The purpose of this study was to identify the grammatical errors made by non-native English teachers when writing narrative texts before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Common errors occur in English writing such as capitalization errors, punctuation errors, grammatical errors, spelling, and supporting arguments (Dobrić et al, 2021;Utami & Mahardika, 2023). This argument supports the students' answer in the interview that most of them experience grammatical errors such as wrong tenses, errors in the use of singular and plural nouns, punctuation, word choice, the use of articles, passive voice, and complex sentences.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Common errors occur in English writing such as capitalization errors, punctuation errors, grammatical errors, spelling, and supporting arguments (Dobrić et al, 2021;Utami & Mahardika, 2023). This argument supports the students' answer in the interview that most of them experience grammatical errors such as wrong tenses, errors in the use of singular and plural nouns, punctuation, word choice, the use of articles, passive voice, and complex sentences.…”
Section: Discussionsupporting
confidence: 66%
“…The Indonesian Journal of the Social SciencesThe advancements in modern technology have greatly facilitated the process of rectifying grammatical faults in written text(Utami & Mahardika, 2023). According toLin et al (2020), AWE, or Automated Writing Evaluation, is a technological tool employed to analyze written content and offer points and criticism Dizon and Gayed, (2021).…”
mentioning
confidence: 99%
“…Meanwhile, AI holds the potential to significantly improve the communication skills of English language learners through the provision of personalized and interactive learning experiences [29]. Moreover, AI tools could undeniably benefit from in-service English retraining, focusing on enhancing their language proficiency [30]. The previous research confirmed that the integration of AI has the potential to benefit students in expanding their English language skills.…”
Section: J Edu and Learnmentioning
confidence: 82%
“…Despite the increasing interest in using AI-powered tools among EFL teachers [22]- [30], little was known about exploring the adoption of AI-powered tools among pre-service teachers using the TPACK framework. There is a need for more exploration of pre-service teachers' technological level of knowledge on integrating AI-powered tools in EFL classrooms, particularly in the Indonesian context.…”
Section: J Edu and Learnmentioning
confidence: 99%